Characteristics of Mulberry Leaf Powder Enriched With γ-Aminobutyric Acid and Its Antioxidant Capacity as a Potential Functional Food Ingredient - Jin, Yingchun; Tu, Jie; Han, Xinyao; Zhuo, Jun; Liu, Guanhui; Han, Yanhui; Du, Hengjun; Wang, Jun; Xiao, Hang (Frontiers in Nutrition, 2022)
To improve the functional properties of mulberry leaves, GABA enrichment treatments were applied. The results showed that the combined treatment of sodium glutamate immersion, cold shock, and anoxic significantly increased the GABA content. HPLC analysis displayed that the quantity of some active phenolics were significantly increased after the treatment.The GABA-enriched mulberry leaf powders were subsequently prepared and it was found that, as the particle size decreased, their water and oil holding capacity and their swelling power decreased, while the angle of repose increased. The dissolution rate of GABA and total phenolics increased as the particle size decreased. Optical observations and SEM results revealed that the fiber structures of the particles were gradually destroyed as the particle size decreased. Further FTIR analysis showed that the active compounds in the powders were not destroyed. M400 and M140 powder showed the maximum DPPH• scavenging ability and AGEs inhibition capacity respectively. Additionally, adding the powders effectively alleviated the staling of bread without significant effect on taste.